PENGARUH EDUKASI GIZI DENGAN MEDIA TEKA-TEKI SILANG DAN VIDEO ANIMASI TERHADAP PENGETAHUAN TENTANG GIZI SEIMBANG PADA ANAK USIA SEKOLAH DI SD NEGERI REMPOA 1 KOTA TANGERANG SELATAN - Andita Arifianita Putri (2022)
Nutritional problems in school-age children can occur because of less knowledge. School-age period is the right time for provide nutrition education to encourage healthy eating habits and behaviors. Nutrition education needs the interesting and fun media to make it easier to understand. Crossword puzzles and animation videos can be used as nutrition educational media. This study aims is to determine the influence of nutrition education with crossword puzzles and animation videos on balanced nutrition knowledge in school-age children in SD Negeri Rempoa 1 Kota Tangerang Selatan. The methods that used is a quasi-experimental with a pretest and posttest group design. The 54 students from grade five were selected by stratified random sampling and divided into two media groups. The results showed that there were differences in the influence of nutrition education before and after being given crossword puzzles (p = 0.003) and animation video (p = 0.000) on balanced nutrition knowledge. The results also showed that there was no difference in the effectiveness of nutrition education between crossword puzzles and animated videos on balanced nutrition knowledge (p = 0.987).